Prediction of flexural behavior of woven reinforced for concrete reinforcement - Putra Jaya, Ramadhansyah; M., Zulkarnain; Z. Z., Mukhtar; N. A., Md Khosim; M. I., Adiyanto; W. I., Mohd Haziman (IOP Publishing Ltd, 2021)
Plain concrete possesses very low tensile strength, limited ductility and little resistance to cracking. Fibers glass-reinforced concrete supposed to improve the strain properties well as crack resistance, ductility, as flexural strength and toughness. This paper aims to predict the flexural behavior of fiber-glass reinforced concrete and optimize the beam design by applying woven layer in M35 grade concrete using finite element method. The several techniques were implemented to study flexural performance, woven position on bottom, middle and upper surface and several woven thickness layers employed to investigate flexural performance such as 5, 10, 20, 30, 40 and 50 mm for beam size of 100 × 100 × 500 mm. It found that the flexural strength increased by positioned the woven on the bottom side and it given the improvement in designing when the layer thickness of fiber varied. It is because the fiber usually reduces the brittleness of concrete by providing post cracking ductility and increase toughness. The difference flexural strength between 50mm and 40mm thickness of fiberglass is about 1.29%.